HDTV in Germany: Lack of Innovation Management Leads to Market Failure - Georg Erber; Sven Heitzler (Weekly Report, 2010)
High definition television may now be poised for a breakthrough in Germany. Unfortunately, in the area of private free-TV, broadcasters and network operators are still blocking each other. Market participants hope to leverage encryption and digital rights management as sources of long-term profits. This, however, may come at the expense of television viewers. Despite the start of regular HDTV operations by public broadcasters, only a few consumers are currently in a position to actually receive high definition television. The government should facilitate a rapid resolution to the current standoff and ensure effective monitoring of competition by implementing new standards.
Keywords: L15; L51; L82; 330; HDTV; Innovation Management; Tragedy of the Anti-Commons